2020
DOI: 10.1084/jem.20190006
|View full text |Cite
|
Sign up to set email alerts
|

Essential cell-extrinsic requirement for PDIA6 in lymphoid and myeloid development

Abstract: In a forward genetic screen of N-ethyl-N-nitrosourea (ENU)–induced mutant mice for aberrant immune function, we identified mice with a syndromic disorder marked by growth retardation, diabetes, premature death, and severe lymphoid and myeloid hypoplasia together with diminished T cell–independent (TI) antibody responses. The causative mutation was in Pdia6, an essential gene encoding protein disulfide isomerase A6 (PDIA6), an oxidoreductase that functions in nascent protein folding in the endoplasmic reticulum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 33 publications
(33 reference statements)
1
21
1
Order By: Relevance
“…The latter is due to the disruption of the critical function of PDIA6 in the development and lineage commitment of hematopoietic cells resulting in an age‐dependent lymphoid and myeloid hypoplasia. Consistent with the infantile‐onset diabetes reported in patients with EIF2AK3 biallelic inactivating variants and EIF2AK3 knockout mice, we showed that the braum/− mice developed a strong phenotype of early‐onset hyperglycemia that was detected as early as 4 weeks of age 3,11,14 …”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…The latter is due to the disruption of the critical function of PDIA6 in the development and lineage commitment of hematopoietic cells resulting in an age‐dependent lymphoid and myeloid hypoplasia. Consistent with the infantile‐onset diabetes reported in patients with EIF2AK3 biallelic inactivating variants and EIF2AK3 knockout mice, we showed that the braum/− mice developed a strong phenotype of early‐onset hyperglycemia that was detected as early as 4 weeks of age 3,11,14 …”
Section: Introductionsupporting
confidence: 89%
“…An N ‐ethyl‐ N ‐nitrosourea (ENU)‐induced missense mutation resulted in a valine (V) to alanine (A) substitution at position 32 (V32A; braum allele) in the first thioredoxin domain of the PDIA6 protein as described previously 3,20 . Heterozygous Pdia6 knockout ( Pdia6 +/− ) mice were generated using the CRISPR/Cas9 system with Pdia6 (5′‐ ACCGCTGACTGCTAGAAAGA‐3′) small base‐pairing guide RNA 21 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations